Revision of the subgenus Parapterygotrigla (Pisces: Triglidae: Pterygotrigla) - Richards, William J.; Yato, Takuji (Zootaxa, 2014)
The subgenus Parapterygotrigla of the triglid genus Pterygotrigla is revised with a description of a new species. The subgenus comprises P. hoplites, P. jacad sp. nov., P. megalops, P. macrorhynchus, P. multiocellata, and P. robertsi. Two juvenile forms considered to be incertae sedis Dixiphichthys ferculum Whitley, and two larval triglids, are discussed together with Trigla brandesii (Bleeker). Members of the subgenus Parapterygotrigla are distributed in tropical waters of the western Pacific and Indian oceans. All species possess a nasal spine, have long and strong nuchal and cleithral spines and short opercular spines. A new species, P. jacad, found in the western Indian Ocean, has an unusually large eye. All members of the subgenus are rare in collections as they live on the bottom in deep water (>200 m) over rough terrain and are rarely taken by trawlers.